Toll-like receptor 9 polymorphisms and Helicobacter pylori influence gene expression and risk of gastric carcinogenesis in the Brazilian population - Susi, Manoela Dias; Caroline, De Matos Lourenço; Rasmussen, Lucas Trevizani; Payão, Spencer Luis Marques; Rossi, Ana Flávia Teixeira [UNESP]; Silva, Ana Elizabete [UNESP]; de Oliveira-Cucolo, Juliana Garcia (Baishideng Publishing Group, 2019)
BACKGROUND Toll-like receptors (TLRs) are the first line of host defense, and are involved in Helicobacter pylori (H. pylori) recognition and activation of both inflammatory and carcinogenic processes. The presence of single nucleotide polymorphisms (SNPs) in genes that activate the immune response may modulate the risk of precancerous lesions and gastric cancer (GC). Among them, Toll-like receptor 9 (TLR9) polymorphisms have emerged with a risk factor of infectious diseases and cancer, however the studies are still inconclusive. AIM To evaluate whether TLR9 rs5743836 and rs187084 SNPs contribute to the risk of gastric carcinogenesis, and its influence on mRNA expression. METHODS A case-control study was conducted to evaluate two TLR9 SNPs (TLR9-1237 TCrs5743836 and TLR9-1486 CT-rs187084) in chronic gastritis (CG) and GC patients. A total of 609 DNA samples of peripheral blood [248 CG, 161 GC, and 200 samples from healthy individuals (C)] were genotyped by polymerase chain reaction-restriction fragment length polymorphism. All samples were tested for the H. pylori infection using Hpx1 and Hpx2 primers. Quantitative polymerase chain reaction by TaqMan® assay was used to quantify TLR9 mRNA from fresh gastric tissues (48 GC, 26 CG, and 14 C). RESULTS For TLR9-1237, the TC + CC or CC genotypes were associated with a higher risk of GC than C [recessive model odds ratio (OR) = 5.01, 95% confidence interval (CI): 2.52-9.94, P < 0.0001], and the CG (recessive model OR =4.63; 95%CI: 2.44- 8.79, P < 0.0001) groups. For TLR9-1486, an association between the CT + TT genotypes and increased risk of both GC (dominant model OR = 2.72, 95%CI: 1.57-4.72, P < 0.0001) and CG (dominant model OR = 1.79, 95%CI: 1.15-2.79, P = 0.0094) was observed when compared to the C group. Moreover, the presence of TLR9-1237 TC/CC + TLR9-1486 CC genotypes potentiate the risk for this neoplasm (OR = 18.57; 95%CI: 5.06-68.15, P < 0.0001). The TLR9 mRNA level was significantly higher in the GC group (RQ = 9.24, P < 0.0001) in relation to the CG group (RQ = 1.55, P = 0.0010) and normal mucosa (RQ = 1.0). When the samples were grouped according to the polymorphic genotypes and the presence of H. pylori infection, an influence of TLR9-1237 TC + CC polymorphic genotypes (P = 0.0083) and H. pylori infection (P < 0.0001) was observed on the upregulation of mRNA expression. CONCLUSION Our findings show that TLR9 rs5743836 and rs187084 polymorphisms are associated with a higher risk of carcinogenesis gastric, and that TLR9 mRNA levels can be modulated by TLR9-1237 TC + CC variant genotypes and H. pylori infection.
Keywords: Chronic gastritis; Gastric cancer; Gene expression; Helicobacter pylori; Polymorphisms; Toll-like receptor 9